Stimuli-responsive polypeptide nanogels for trypsin inhibition - Šálek, Petr; Dvořáková, Jana; Hladysh, Sviatoslav; Oleshchuk, Diana; Pavlova, Ewa; Kučka, Jan; Proks, Vladimír (Beilstein journal of nanotechnology, 2022)
A new type of hydrophilic, biocompatible, and biodegradable polypeptide nanogel depots loaded with the natural serine protease inhibitor α1-antitrypsin (AAT) was applied for the inhibition of the inflammatory mediator trypsin. Two types of nanogels were prepared from linear synthetic polypeptides based on biocompatible and biodegradable poly[N 5-(2-hydroxyethyl)-ʟ-glutamine-ran-N 5-propargyl-ʟ-glutamine-ran-N 5-(6-aminohexyl)-ʟ-glutamine]-ran-N 5-[2-(4-hydroxyphenyl)ethyl)-ʟ-glutamine] (PHEG-Tyr) or biocompatible N α-ʟ-lysine-grafted α,β-poly[(2-propyne)-ᴅ,ʟ-aspartamide-ran-(2-hydroxyethyl)-ᴅʟ-aspartamide-ran-(2-(4-hydroxyphenyl)ethyl)-ᴅʟ-aspartamide] (N α-Lys-NG). Both nanogels were prepared by HRP/H2O2-mediated crosslinking in inverse miniemulsions with pH and temperature-stimuli responsive behavior confirmed by dynamic light scattering and zeta potential measurements. The loading capacity of PHEG-Tyr and N α-Lys-NG nanogels and their release profiles were first optimized with bovine serum albumin. The nanogels were then used for loading and release of AAT. PHEG-Tyr and N α-Lys-NG nanogels showed different loading capacities for AAT with the maximum (20%) achieved with N α-Lys-NG nanogel. In both cases, the nanogel depots demonstrated a burst release of AAT during the first 6 h, which could be favorable for quick inhibition of trypsin. A consequent pilot in vitro inhibition study revealed that both PHEG-Tyr and N α-Lys-NG nanogels loaded with AAT successfully inhibited the enzymatic activity of trypsin. Furthermore, the inhibitory efficiency of the AAT-loaded nanogels was higher than that of only AAT. Interestingly, also non-loaded PHEG-Tyr and N α-Lys-NG nanogels were shown to effectively inhibit trypsin because they contain suitable amino acids in their structures that effectively block the active site of trypsin.
Keywords: inflammatory mediator; nanogel; trypsin; polypeptide; α1-antitrypsin